Ionotropic Glutamate Receptors IR64a and IR8a Form a Functional Odorant Receptor Complex In Vivo in Drosophila. - Ai, M.; Blais, S.; Park, J.Y.; Min, S.; Neubert, T.A.; Suh, G.S. (Journal of Neuroscience, 2013)
Drosophila olfactory sensory neurons express either odorant receptors or ionotropic glutamate receptors (IRs). The sensory neurons that express IR64a, a member of the IR family, send axonal projections to either the DC4 or DP1m glomeruli in the antennal lobe. DC4 neurons respond specifically to acids/protons, whereas DP1m neurons respond to a broad spectrum of odorants. The molecular composition of IR64a-containing receptor complexes in either DC4 or DP1m neurons is not known, however. Here, we immunoprecipitated the IR64a protein from lysates of fly antennal tissue and identified IR8a as a receptor subunit physically associated with IR64a by mass spectrometry. IR8a mutants and flies in which IR8a was knocked down by RNAi in IR64a+ neurons exhibited defects in acid-evoked physiological and behavioral responses. Furthermore, we found that the loss of IR8a caused a significant reduction in IR64a protein levels. When expressed in Xenopus oocytes, IR64a and IR8a formed a functional ion channel that allowed ligand-evoked cation currents. These findings provide direct evidence that IR8a is a subunit that forms a functional olfactory receptor with IR64a in vivo to mediate odor detection.